2021
DOI: 10.21203/rs.3.rs-444161/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resilience to COVID-19: Socioeconomic Disadvantage Associated With Higher Positive Parent-youth Communication and Youth Disease-prevention Behavior

Abstract: Socioeconomic disadvantage is associated with larger COVID-19 disease burdens and pandemic-related economic impacts. We utilized the longitudinal Adolescent Brain Cognitive Development Study to understand how family- and neighborhood-level socioeconomic disadvantage relate to disease burden, family communication, and preventative responses to the pandemic in over 6,000 youth-parent/caregiver dyads. Data were collected at three timepoints (May to August 2020). Here, we show that both family- and neighborhood-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Sleep difficulties are well-documented risk factors for depressed mood, implicating sleep as a promising modifiable factor for preventing mood deficits [ 21 ] and improving depression outcomes [ 22 ]. Another crucial factor in the prevention and recovery of psychopathology in young people that could be critical in the context of the pandemic is adaptive coping strategies in response to life stress [ 23 , 24 , 25 ]. Longitudinal analyses of 1251 adolescents [ 24 ] revealed that the association between poorer coping strategies and depressive symptoms increased after the age of 17.5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep difficulties are well-documented risk factors for depressed mood, implicating sleep as a promising modifiable factor for preventing mood deficits [ 21 ] and improving depression outcomes [ 22 ]. Another crucial factor in the prevention and recovery of psychopathology in young people that could be critical in the context of the pandemic is adaptive coping strategies in response to life stress [ 23 , 24 , 25 ]. Longitudinal analyses of 1251 adolescents [ 24 ] revealed that the association between poorer coping strategies and depressive symptoms increased after the age of 17.5 years.…”
Section: Introductionmentioning
confidence: 99%